Adaptation of the balanced scorecard model to measure performance of the departments at Dr Zainoel Abidin Regional General Hospital, Banda Aceh. (10th January 2020) - Martunis, Ashiva; Dalimunthe, Ritha; Amalia, Khaira; Juanita, Juanita; Syahputra, Hendra; Adam, Muhammad; Masyudi, Masyudi
Abstract : Purpose: This paper aims to determine the performance of the departments at Dr Zainoel Abidin Regional General Hospital, Banda Aceh, Indonesia, in 2016, based on the targets and realization of their work programs using balanced scorecard. Design/methodology/approach: This study adopted qualitative and quantitative approaches. Findings: The overall results of the performance appraisal using the balanced scorecard approach seen from the financial, internal business, customer and training and learning perspectives are good. Dr Zainoel Abidin Regional General Hospital has provided good services, and performance of its departments have generated the expected outcome, realized by the Hospital. Originality/value: The novelty of the present study lies in its research model, where human resources (transformational leadership, organizational commitment and resource uniqueness) and financial management (business plans, budget and performance).